The Influence of the Physical Work Environment and Work Discipline on Employee Performance at the Tegal District Health Office - Malviana Febriyani; Ratna Komala Putri (Universitas KH. Abdul Chalim Mojokerto, 2024)
The Tegal District Health Service is responsible for health matters but experiences yearly fluctuations in employee performance. This research aims to evaluate the condition of the physical work environment, work discipline, and employee performance and examine the influence of these two factors on employee performance. Using a descriptive approach with quantitative data, this research involved 101 employee respondents through interviews, questionnaires, and observations. The results show that the physical working environment is considered conducive (80.6%), work discipline is very disciplined (86.2%), and employee performance is good (80.9%). The physical work environment does not have a significant effect on employee performance, while work discipline has a significant effect on employee performance. Simultaneously, both factors have a substantial impact on employee performance. These findings are useful for academics and the Tegal District Health Service to improve employee performance through improving the physical work environment and work discipline. Further research is expected to develop new variables and methods for broader results.